Modeling of the Density, Viscosity and Electrical Conductivity of Aqueous Solutions Saturated in Boric Acid in Presence of Lithium Sulfate or Sodium Sulfate at 293.15 to 313.15 K - Soto-Gomez, J (Elsevier B.V., 2021)
The modeling of the density, viscosity and electrical conductivity of aqueous solutions saturated with boric acid, in the presence of sodium sulfate or lithium sulfate, are presented. The salt concentrations range studied were from (0 to 3.3242) mol·kg−1 for sodium sulfate and from (0 to 2.9336) mol·kg−1 for lithium sulfate at temperatures from (293.15 to 313.15) K and at 1 atm pressure. A model for the density was derived using the Pitzer model. The Eyring s absolute rate theory and the Pitzer model were combined to represent the viscosity. The Casteel-Amis equation was modified to describe the electrical conductivity with temperature and boric acid effects where necessary. The results showed that the models successfully represented the properties studied and are robust for estimation purposes within and beyond the experimental range studied. Also, it was found that short range interactions of boric acid, sulfate, sodium and lithium ions with water molecules are relevant to determine the volumetric and transport properties of these solutions and that the electrical conductivity is determined by charged species (Na+, SO42−, NaSO4−, HSO4− and Li+, SO42−, LiSO4−) and the solution viscosity; that is mainly influenced by these salts concentrations, boric acid solubility behavior with these salts and temperature. This is valuable information to improve the processes of boric acid production. © 2020